The Effectiveness of Basic Dance Movement Therapy on the Completeness of Motoric Skill in Preschool Children - Sambodo Sriadi Pinilih; M. Khoirul Amin; Evi Rositasari (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Motor development is one aspect of development that can integrate the development of other aspects. If the developmental aspect is not stimulated, the child's development will be delayed, so the child will have difficulty in following the learning process in elementary school. Basic Dance Movement Therapy is the provision of independent therapy. This study aims to determine the effectiveness of Basic Dance Movement Therapy on the Completeness of Motoric Skill in Preschool Children. This study used quasi-experimental with one group pre-post design. The sampling technique was Proportionate Stratified Random Sampling with a sample size of 58 children studying at Aisyiyah Playgroup, at Jamblang, Kaliabu Village, Salaman District and Az-Zahra NU Playgroup, Salaman District. Data analysis was performed using univariate and bivariate analysis with the Wilcoxon statistical test. There was a significant effectiveness of Basic Dance Movement Therapy and the completeness of motor skills of preschool children in Aisyiyah Playgroup, Jamblang, Kaliabu Village, Salaman District and Az-Zahra NU Playgroup, Salaman, with a p-value of 0.000 (p <0.05). Basic Dance Movement Therapy is effective to improve the children's motoric skills. Suggestion: This study can be used as the basic for further research, namely modified therapy under normal conditions or combined with other methods that can be done online or offline.